Alien Fish Species in the Mbô Floodplain Rivers in Cameroon. (13th August 2018) - Tiogué, Claudine Tekounegning; Nguenga, David; Tomedi-Tabi, Minette Eyango; Tekwombuo, Joseph; Tekou, Guegang; Tchoumboué, Joseph
Abstract : The aim of this study was to identify different alien fish species introduced in the Mbô Floodplain (MF) Rivers in Cameroon and to study their life-history traits. For this purpose, a total number of 237 fishes with a total length (TL) of 24.50 ± 5.97 cm and total weight of 199.50 ± 106.78 g collected by traditional fishing gears were used for taxonomic identification. Four species grouped into three families were identified: Clariidae ( Clarias gariepinus ), Cichlidae ( Oreochromis niloticus and Tilapia cameronensis ), and Channidae ( Parachanna obscura ). There are two types of fish introduction: accidental introduction and intentional transfer. All fish species collected and examined were of large sizes (TL > 25 cm). The regression coefficient b of the length-weight relationship ranged from 3.00 ( C. gariepinus ) to 3.37 ( T. cameronensis ) (3.18 ± 0.17). Fish species showed a monthly and seasonal fluctuation in abundance in number of individuals. Alien fish species in the Mbô Floodplain showed two types of somatic growth: isometric and positive allometric. 75% of overall alien fish species were established and they recorded a mean K factor of 0.70 ± 0.40. Only 25.00% of the sampled species had more females than males.